Synthesis and characterization of a high-affinity α(v)β(6)-specific ligand for in vitro and in vivo applications - Li, Shunzi (2009)
The α(v)β(6) integrin is an attractive therapeutic target for several cancers due to its role in metastasis and its negligible expression in normal tissues. We previously identified a peptide from a phage-displayed peptide library that binds specifically to α(v)β(6). The tetrameric version of the peptide has higher affinity for its cellular targets than the corresponding monomers. However, the inefficient synthesis limits its clinical potential. We report here a convergent synthesis producing the tetrameric peptide in high yield and purity. The ease of the synthesis allows for rapid optimization of the peptide. We have optimized this α(v)β(6) integrin–binding peptide, determining the minimal binding domain and valency. Importantly, the half-maximal binding affinity of the optimal peptide for its target cell is in the 40 to 60 pmol/L range, rivaling the affinity of commonly used antibody-targeting reagents. This peptide mediates cell-specific uptake, is functional in diagnostic formats, is stable in sera, and can home to a tumor in an animal. We anticipate that this high-affinity ligand for α(v)β(6) will find clinical use as a diagnostic and therapeutic reagent.